A nitrogen-doped nanotube molecule with atom vacancy defects - Koki Ikemoto (Nature Portfolio, 2020)
Replacing carbon atoms in nanocarbons with heteroatoms alters their intrinsic properties, and nitrogen-doped nanocarbons attract much attention in various fields. Here, the authors synthesize a discrete nitrogen-doped nanotube molecule and clarify its structure to reveal unique features of nitrogen dopants.